European consumer and societal stakeholders' response to crop improvements and new plant breeding techniques. Issue 1 (30th September 2022) - Nair, Abhishek; Fischer, Arnout R. H.; Moscatelli, Silvana; Socaciu, Carmen; Kohl, Christian; Stetkiewicz, Stacia S.; Menary, Jonathan; Baekelandt, Alexandra; Nanda, Amrit K.; Jorasch, Petra; Davies, Jessica A. C.; Wilhelm, Ralf
Abstract: The global demand for providing nutritious, sustainable, and safe diets for a 10 billion population by 2050 while preserving affordability, reducing environmental impacts, and adapting to climate change will require accelerating the transition to sustainable agri‐food systems. A plausible way to help tackle these challenges is by developing new plant varieties that have improved crop yield, plant nutritional quality, and sustainability (or resilience) traits. However, stakeholders, consumers, and citizens' concerns and appreciation of future‐proofing crops and the acceptability of new plant breeding strategies are not well‐established. These groups are actors in the agri‐food systems, and their views, values, needs, and expectations are crucial in helping to co‐design fair, ethical, acceptable, sustainable, and socially desirable policies on new plant breeding techniques (NPBTs) and the transition to sustainable agri‐food systems. In this study, we engaged with consumer experts and societal stakeholders to consider their perceptions, expectations, and acceptability of improving crops and NPBTs for future‐proofing the agri‐food systems. Our analysis points to a need for governments to take a proactive role in regulating NPBTs, ensure openness and transparency in breeding new crop varieties, and inform consumers about the effects of these breeding programmes and the risks and benefits of the new crop varieties developed. Consumer experts and societal stakeholders considered these strategies necessary to instil confidence in society about NPBTs and accelerate the transition to sustainable agri‐food systems. Abstract : Stakeholders, consumers and citizens' concerns and appreciation of future‐proofing crops and the acceptability of new plant breeding strategies are not well‐established. These groups are actors in the agri‐food systems, and their views, values, needs, and expectations are crucial for co‐designing fair, ethical, acceptable, sustainable, and socially desirable policies on New Plant Breeding Techniques (NPBTs) and transitioning to sustainable agri‐food systems. In this study, we engaged with consumer experts and societal stakeholders to consider their perceptions, expectations, and acceptability of improving crops and NPBTs for future‐proofing the agri‐food systems.